Black tea benefits short‐chain fatty acid producers but inhibits genus Lactobacillus in the gut of healthy Sprague–Dawley rats. (18th August 2020) - Gao, Ying; Xu, Yongquan; Yin, Junfeng
Abstract: BACKGROUND: The gut microbiota plays important roles in physiological and pathological processes of the host. The effect of black tea on the gut microbiota of healthy individuals remains unclear. RESULTS: Healthy Sprague–Dawley (SD) rats were given black tea for 4 weeks, and cecum content, serum, intestinal, and hepatic samples were collected. The results showed that black tea increased α‐diversity and modulated β‐diversity of the gut microbiota. Additionally, black tea enriched several short‐chain fatty acid (SCFA) producers but suppressed genus Lactobacillus . Further tests revealed that the enrichment of SCFA producers was associated with a decrease in the oxidative stress of cecum content caused by black tea, and related to increased luminal butyric acid levels and enhanced intestinal barrier function. The suppression of genus Lactobacillus was related to the increase in luminal total bile acids caused by black tea. In vitro tests showed that bile acids rather than black tea directly inhibited Lactobacillus strains. The reduction in genus Lactobacillus did not affect the effects of black tea on intestinal barrier function and lipid levels. CONCLUSION: Our results imply that the effects of black tea on gut microbiota in healthy individuals are complex and provide a new perspective on the associations among black tea, gut microbiota, and health. © 2020 Society of Chemical Industry